Parental support behaviors for children participating in community soccer programs - Taylor, A. C.; Schweichler, J. T.; Jorgensen, B. L.; McKown, E. H.; Teresak, M. (The Sport Journal, 2014)
The current study examined the perceptions of parental supportive behaviors and activities when children are involved in community recreational soccer programs. A sample of 145 parents completed the online survey. Children ranged in age from 3-18 years old and had a mean age of 6.02 (SD= 0.86). Demographic information was gathered and twenty supportive behavior statements with likert-type scales were drawn from four general support categories: Instrumental Support, Communicative Support with Coaches, Communicative Support during Games, and Communicative Support with Child Before and After Games. Results indicated that parents were most likely to perform Instrumental Support types of behaviors (M=4.55) which included supportive activities such as attending games and practices, purchasing proper soccer equipment, and bringing game snacks. Attending their child`s soccer game (M=4.81, SD = 0.39), showing love and affection to the child who is upset and disappointed after a game (M=4.71, SD = 0.47), and purchasing and providing the correct soccer equipment (M=4.70, SD = .053) were the top-ranked parental supportive behaviors. Freely voicing frustration/opinions during the game when disagreeing with a coach`s decision (M=1.49, SD = 0.68) was ranked the lowest among all supportive behaviors. The results suggest that the goals parents have for their soccer playing children center around positive social development. Parental actions and behaviors related to visible and verbal encouragement were rated very highly as supportive activities while voicing frustration at coaches, children`s teammates, referees and their own children were rated among the lowest. These results may lead to potential collaboration between parents and coaches regarding the development of their players and children.